Poor Girls are Vulnerable to be Married: A Case Study of Dayak Mali Law in West Kalimantan - Nikodemus Niko (Yayasan Jurnal Perempuan, 2016)
This paper investigates the child-marriage in West Kalimantan. This study took Desa Cowet who is inhabited mainly by Dayak Mali. The issue of child-marriage is perpetuated by the Law in Indonesia. The effort to eliminate child-marriage is often difficult due to the high-rate of poverty among Dayak Mali people. Within Indigenous Law, there is no specific rules that arrange child-marriage or age of minimum to marriage. What is stated is usually the approval of both parents to the couple. Child-marriage among Dayak Mali, this study confirmed, is basically mostly triggered by poverty of girls in villages. Poor girl of Dayak Mali are basically prone to child-marriage.